Modern Aesthetics In Balinese Sculpture: A Case Study Of Wayan Jana - I Putu Sinar Wijaya; I Wayan Gede Budayana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Sculpture is one of the arts that requires special skills from a sculptor, sculptor or usually known as a sculpture craftsman. Usually makes works from rock and wood; nowadays, various materials can be used, such as temple stone or volcanic lava stone. Sculptors choose one material to be made into a statue, and it becomes a characteristic of their work. One of the young Balinese sculptors who continues to restlessly search for and find new ideas in sculpture is Wayan Jana. With aesthetic theory being the choice to dissect this sculpture, where beauty is the benchmark in examining this sculpture, starting from composition, proportion, and space, the sculpture that is used as the research material is a work with a modern style seems elastic and dynamic. The sculptures of artist I Wayan Jana have a very modern style, displaying the forms of living creatures such as humans and animals. The style displayed distorts the original form into the form of the artist's own imagination. With such compositions, the resulting sculptures are inseparable from the aesthetic values ​​​​presented in each work created. Although most of Jana's works this time talk about love, he is able to maintain the forms of his work so as not to become verbal. Jana's works that seem elastic and dynamic still provide space for the imagination of the viewer. The images that appear are very dependent on the experience and strength of the viewer's imagination.